DEVELOPMENT OF INTERACTIVE VIDEOS TO IMPROVE ROAD SAFETY FOR STUDENTS WITH INTELLECTUAL DISABILITIES (International Journal of Cultural and Social Science, 2026)
This study aims to identify the basic needs in developing interactive video media as a tool for problem-based learning to enhance road safety awareness among students with intellectual disabilities, to produce feasible interactive video media, and to create effective interactive videos. The study employed the ADDIE development model. The subjects of this research were ten students with intellectual disabilities. Data collection techniques included interviews, expert validation questionnaires, teacher response questionnaires, and road safety comprehension tests. The data were analyzed using both qualitative and quantitative methods. The results of the study indicate that: (1) the interactive video product was designed with various features, including motion animation, image animation, text, audio, and factual videos tailored to the needs of the students. The material expert validation yielded a score of 79.5 (Very Good), while the media expert validation scored 82 (Very Good). (2) The interactive video was effective for students with intellectual disabilities, as evidenced by an improvement in test scores of 39% and an increase in students' comprehension of road safety.